Epidemiology of injuries in senior men`s field hockey: A two-season prospective observational injury surveillance study - Rees, H.; McCarthy Persson, U.; Delahunt, E.; Boreham, C.; Blake, C. (Journal of Sports Sciences, 2020)
Determining the rate and severity of injuries incurred through sport is accepted as the primary step towards designing, implementing and evaluating injury prevention programmes. The aim of this study was to determine the injury incidence rate and characteristics of male field hockey athletes participating in the Irish Hockey League. Athletes from eight field hockey teams were assigned to an online reporting system, where they logged injuries as they were incurred. Injuries were defined as any physical complaint. Coaches and physiotherapists were contacted weekly to corroborateinjuries. Overall 323 injuries were reported across 34,449 exposure hours, giving rise to an incidence rate of 9.4/1000 h. On average, athletes sustained one injury over the course of two seasons. Muscle strains, pain and contusions were the most common types of injury, while the hamstring, knee and hip/groin were the most frequently reported locations. While 66.9% of injuries occurred through non-contact mechanisms, contact injuries were also common. Injury recurrences accounted for 16.1% of injuries. In conclusion, the incidence of injury in field hockey is high, occurring from a variety of mechanisms. Future injury prevention strategies should prioritise injuries to the hamstring, knee and ankle, and be specific to particular playing positions.